Operational Modal Analysis for Crack Detection in Rotating Blades - BEDNARZ, Jarosław (Archives of Acoustics, 2017)
Vibration analysis has found widespread application for condition monitoring in a variety of applications and industries. With the continual development of cheaper and more powerful processing hardware, such systems have developed from utilizing simple checks on amplitude to those based around sophisticated spectral analysis. The paper presents application of the model based diagnostic method for early detection of faults in rotating machinery. The proposed diagnostics system based on modal analysis methods (OMA and OMAX methods). In the paper the diagnostic system based on such modelling is presented. The proposed system was verified during research on a specialized test rig, which can generate vibration signals.